INFLUENCE OF COBALT CONTENT ON CURIE TEMPERATURE OF THE ALLOY Fe43+xCo29-xY8B20 WHERE x = 0 OR 5 - Kinga JEZ (European Journal of Materials Science and Engineering, 2018)
The paper presents the original results of studies on rapidly cooled alloys with chemical composition Fe43+xCo29-xY8B20 where x = 0 or 5. The alloys were made by sucking a liquid alloy into the copper mold. Samples were made in the shape of 10mm x 5mm x 0.5mm plates. The structure of the obtained alloys was examined by X-ray diffraction. The magnetic polarization of saturation as a function of temperature was measured using the Faraday magnetic weight. The measured curves 0s (T) shows one gentle inflection from the transition from ferro to paramagnetic. On the basis of the numerical analysis of the obtained curves, the Curie temperatures of the studied alloys were determined. Significant influence of cobalt content on Curie temperature of amorphous alloys was confirmed. The tests confirmed good glass ability of alloys based on FeCoBY using a relatively low cooling rate (order of 102K/s).